(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India has been a favorite destination for people all over the world. It has been frequently visited by a lot many writers among whom a few are renowned travel writers of this century. Travel literature may be cross-cultural or transnational in focus, or can involve travel to different regions within the same country. The present study is a step towards this unexplored area. All the secondary sources, journals, articles and reviews would be of immense help in this work. Greater symmetry with regard to religion specifically can be found in the work of writers who have acknowledged the influence of Naipaul on their development as writers, especially Amitav Ghosh and Amitava Kumar. Along with symmetry, there is a clear sense of mission in these writers’ works that challenges Naipaul’s passivity. For some Indian literary secularists, at least, the task of the writer is not merely to diagnose the problem but to participate in some fashion in resolving it. Dalrymple though an outsider has truly encapsulated the paradigm of Indian religion in its true entirety through his novel Nine Lives. The present thesis examines India and its people in the travel writings of V.S. Naipaul and William Darlymple at length.